The effectiveness of internet chat groups in relapse prevention after inpatient psychotherapy - Bauer, Stephanie; Wolf, Markus; Haug, Severin; Kordy, Hans (Psychotherapy research, 2011)
The majority of patients benefit from psychotherapeutic treatment. However, many fail to maintain their treatment gains following discharge. In a controlled study, we investigated the effectiveness of internet chat groups in preventing relapse following inpatient treatment. One hundred and fifty-two patients were assessed with the Longitudinal Follow-up Evaluation (LIFE) 1 year after discharge from the hospital. Kaplan Meier survival analyses showed that significantly fewer chat participants (22.2%) than control participants (46.5%) experienced a relapse. Additional analyses yielded a significant difference in the relapse rates of chat and control participants depending on their utilization of outpatient treatment after discharge. The results confirm that technology-enhanced interventions are effective in maintaining treatment gains. Implications of the findings for health care provision are discussed.